2013
DOI: 10.1021/jm400193d
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Inhibition of the Fat Mass and Obesity Associated Protein (FTO)

Abstract: The fat mass and obesity associated protein (FTO) is a potential target for anti-obesity medicines. FTO is a 2-oxoglutarate (2OG)-dependent N-methyl nucleic acid demethylase that acts on substrates including 3-methylthymidine, 3-methyluracil, and 6-methyladenine. To identify FTO inhibitors, we screened a set of 2OG analogues and related compounds using differential scanning fluorometry- and liquid chromatography-based assays. The results revealed sets of both cyclic and acyclic 2OG analogues that are FTO inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
201
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(208 citation statements)
references
References 33 publications
(67 reference statements)
4
201
1
Order By: Relevance
“…The IC 50 of citrate for ALKBH5 was measured at 488 M, which is comparable to that for human FTO (300 M) under standard assay conditions (Fig. 4D) (35). Therefore, although citrate is observed to adopt different binding modes in the FTO and ALKBH5 crystal structures, it can act as an inhibitor for both human m 6 A demethylases.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The IC 50 of citrate for ALKBH5 was measured at 488 M, which is comparable to that for human FTO (300 M) under standard assay conditions (Fig. 4D) (35). Therefore, although citrate is observed to adopt different binding modes in the FTO and ALKBH5 crystal structures, it can act as an inhibitor for both human m 6 A demethylases.…”
Section: Resultssupporting
confidence: 52%
“…Recently, Aik et al (35) reported that citrate can act as a modest inhibitor of the human ALKBH enzyme FTO. In the FTO-citrate complex structure, the citrate molecule binds to FTO in a different manner, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BA is a moderate inhibitor of FTO (Fig. 1B) (31,49). AlkB repair remained intact, however, even in the presence of 100-fold excess BA (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…5B). In contrast, rhein fully occupies the methylated DNA binding site in FTO (49). The structural superimposition of FTO and the complex of rhein bound to AlkB clearly shows that rhein would not bind to the 2OG pocket of FTO because of steric clashes to Tyr 295 and Met 297 (Fig.…”
Section: Resultsmentioning
confidence: 98%